A Multidisciplinary Approach to Pancreas Cancer in 2016: A Review. (April 2017) - Fogel, Evan L; Shahda, Safi; Sandrasegaran, Kumar; DeWitt, John; Easler, Jeffrey J; Agarwal, David M; Eagleson, Mackenzie; Zyromski, Nicholas J; House, Michael G; Ellsworth, Susannah; El Hajj, Ihab; O'Neil, Bert H; et al.
Abstract : N/A: In this article, we review our multidisciplinary approach for patients with pancreatic cancer. Specifically, we review the epidemiology, diagnosis and staging, biliary drainage techniques, selection of patients for surgery, chemotherapy, radiation therapy, and discuss other palliative interventions. The areas of active research investigation and where our knowledge is limited are emphasized.